1974
DOI: 10.1111/j.1348-0421.1974.tb00951.x
|View full text |Cite
|
Sign up to set email alerts
|

Typing of Herpes Simplex Virus Strains of Genital and Nongenital Origins

Abstract: Herpes simplex virus strains isolated from genital and nongenital sites were classified into type 1 (HSV-1) and type 2 (HSV-2) by endpoint neutralization tests using IgM of rabbits hyperimmunized with either HF (HSV-1) or UW-268 (HSV-2) strain. It was found that about one-third of the genital isolates belonged to type 1, in contrast to the general concept that HSV-2 represents genital herpes strains. These HSV-1 strains, differing from HSV-2, were mostly isolates from acute herpetic lesions of female patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

1975
1975
2005
2005

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…The HF strain of HSV-1 and the UW-268 strain of HSV-2 (34), which had been maintained by passage through Vero cells were used. Virus infectivity was expressed by the tissue-culture-infective dose (TCD) as determined by the microtitration method described earlier (14). For immunization of animals, culture fluids of infected HeLa cells were used.…”
Section: Methodsmentioning
confidence: 99%
“…The HF strain of HSV-1 and the UW-268 strain of HSV-2 (34), which had been maintained by passage through Vero cells were used. Virus infectivity was expressed by the tissue-culture-infective dose (TCD) as determined by the microtitration method described earlier (14). For immunization of animals, culture fluids of infected HeLa cells were used.…”
Section: Methodsmentioning
confidence: 99%
“…Difference in plaque-forming ability or plaque appearance between herpes simplex virus type 1 (HSV1) and type 2 (HSV2) had been studied in various cell culture systems1, 2,7,12,13,15), and are considered to be a biological marker distinguishing one from the other. Especially, primary chick emblryonic fibroblasts (CEF) are known to have unique characteristics for identifing HSV1 and HSV2.…”
Section: Introductionmentioning
confidence: 99%
“…Most HSV1 isolates produce no plaques or small plaques on CEF. In contrast, large plaques are formed on CEF by HSV2 strains from the first passage of the virus2, 7,12). CEF culture systems accompanied by other kinds of cell cultures were used to distinguish HSV1 from HSV2 in a clinical laboratory14) or to select temperature-sensitive mutants for the study of pathogenicity in guinea pigsl).…”
Section: Introductionmentioning
confidence: 99%
“…However, most of the criteria thus far reported on which to differentiate the two types have been based on quantitative rather than qualitative differences, except the presence of tubular structures in type 2 herpes simplex virus (HSV-2)-infected cells [1] and density of viral DNA [3,6]. We have searched for a simple routine procedure to determine the types of HSV isolates and found that the chick embryo (CE) cell plaque marker [2,8] was suited for this purpose [5]. Yet this marker also measured a quantitative difference and showed a disadvantage that a strain experiencing serial egg or CE cell passages might possibly be mistyped.…”
mentioning
confidence: 99%
“…Type determination of these isolates was based on neutralization by specific hyperimmune rabbit IgM in the presence of complement [4]. Passage histories of the strains were detailed elsewhere [5]. Virus stocks were prepared in Vero cells, the culture fluids being shell-frozen in glass ampoules and stored at -70 C.…”
mentioning
confidence: 99%